The Influence of Science, Environment, Technology, Society (SETS) Learning Models on Learning Activities and Biology Learning Outcomes - Jumiah Az; Indayana Febriani Tanjung; Rohani Rohani (Jurnal Pendidikan Biologi, 2022)
This study aims to determine the effect of the Science, Environment, Technology, Society (SETS) learning model on learning activities and biology learning outcomes. The sample of this research was students of class VII totaling 30 students people. The research data collection method is using data collection instruments in the form of learning activity observation and a written test in the form of multiple choice. Methods of data analysis of learning activities using the formula Weight Means Score and data analysis of learning outcomes is done by using the "ttest" test. The average result of the interpretation score is 3.30 with the interpretation number criteria interval from 3.25 to 4.00. The mean rate of this interpretation means that it falls into the “Very Active” criterion. The prerequisite test proved to be normally distributed and homogeneous. The results of the ttest test calculation show that t count is 2.265 and t table is 2.048, so from these values it can be concluded that t count> t table. Based on the research results, it can be concluded that there is an influence of the science, environment, technology, society (SETS) learning model on biology learning activities. The benefit of this research is that it can find the right learning model to be applied to plant material and can be used as a reference for teachers in delivering material.